Therapy with high-dose Interleukin-2 (HD IL-2) in metastatic melanoma and renal cell carcinoma following PD1 or PDL1 inhibition. Issue 1 (18th February 2019) - Buchbinder, Elizabeth I.; Dutcher, Janice P.; Daniels, Gregory A.; Curti, Brendan D.; Patel, Sapna P.; Holtan, Shernan G.; Miletello, Gerald P.; Fishman, Mayer N.; Gonzalez, Rene; Clark, Joseph I.; Richart, John M.; Lao, Christopher D.; et al.
Abstract : Background: Metastatic melanoma (mM) and renal cell carcinoma (mRCC) are often treated with anti-PD-1 based therapy, however not all patients respond and further therapies are needed. High dose interleukin-2 (HD IL-2) can lead to durable responses in a subset of mM and mRCC patients. The efficacy and toxicity of HD IL-2 therapy following anti-PD-1 or anti-PD-L1 therapy have not yet been explored. Methods: Reports on mM and mRCC patients who had received HD IL-2 after PD-1 or PD-L1 inhibition were queried from the PROCLAIM SM database. Patient characteristics, toxicity and efficacy were analyzed. Results: A total of 57 patients (40 mM, 17 mRCC) were treated with high dose IL-2 after PD-1 or PD-L1 inhibition and had data recorded in the PROCLAIM database. The best overall response rate to HD IL-2 was 22.5% for mM (4 complete response (CR), 5 partial responses (PRs)) and 24% for mRCC (2 CRs, 2 PRs). The toxicity related to HD IL-2 observed in these patients was similar to that observed in patients treated with HD IL-2 without prior checkpoint blockade. One patient who had received prior PD-L1 blockade developed drug induced pneumonitis with HD IL-2 requiring steroid therapy. Conclusion: In this retrospective analysis, HD IL-2 therapy displayed durable antitumor activity in mM and mRCC patients who progressed following treatment with PD-1 and PD-L1 inhibition. The toxicities were generally manageable and consistent with expectations from HD IL-2 but physicians should watch for immune related toxicities such as pneumonitis. This analysis supports the development of randomized prospective trials to assess the proper sequencing and combination of immune checkpoint blockade and cytokine therapy.